2022
DOI: 10.1038/s41467-021-27322-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of human primary prostate cancer reveals the heterogeneity of tumor-associated epithelial cell states

Abstract: Prostate cancer is the second most common malignancy in men worldwide and consists of a mixture of tumor and non-tumor cell types. To characterize the prostate cancer tumor microenvironment, we perform single-cell RNA-sequencing on prostate biopsies, prostatectomy specimens, and patient-derived organoids from localized prostate cancer patients. We uncover heterogeneous cellular states in prostate epithelial cells marked by high androgen signaling states that are enriched in prostate cancer and identify a popul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
135
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 99 publications
13
135
0
Order By: Relevance
“…We used RNA velocity to infer the likely trajectories of epithelial cell differentiation (21,22). One trajectory suggested that club cells act as luminal cell progenitors, an observation previously reported in prostate cancer (23). A second distinct trajectory showed consistent directional flow suggesting that hillock cells may be acting as progenitors for basal cells (Figure 2B).…”
Section: A Prostate Tumor Gene Signature Distinguishes Normal and Mal...mentioning
confidence: 75%
See 2 more Smart Citations
“…We used RNA velocity to infer the likely trajectories of epithelial cell differentiation (21,22). One trajectory suggested that club cells act as luminal cell progenitors, an observation previously reported in prostate cancer (23). A second distinct trajectory showed consistent directional flow suggesting that hillock cells may be acting as progenitors for basal cells (Figure 2B).…”
Section: A Prostate Tumor Gene Signature Distinguishes Normal and Mal...mentioning
confidence: 75%
“…Regarding epithelial cells, we identified distinct subsets of hillock and club cells that have been described in normal prostate tissue (5,7,20). Club cells have been identified in human prostate tumors (23); however, we are the first to show and characterize the hillock cells in human prostate tumors ( Figure 2B ). Our RNA velocity analysis suggested a progenitor role for club cells which has been previously reported (23).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…NO, as synthesized by eNOS and derived from endothelial cells, has been shown to promote the angiogenesis in tumor tissues [ 61 ]. However, one recent single-cell sequencing study shows that the proportion of endothelial cells in the prostate tumor tissues is quite low (less than 7% of total cell population), in 6 out of 7 localized prostate tumors obtained by radical prostatectomy [ 62 ], and thus their possible contribution in terms of eNOS-NO production to the growth of tumor cells or PCSCs is believed to be minimal. Moreover, emerging evidence demonstrates that PCSCs are resistant to androgen deprivation therapy and their expansion in cell population during the advanced progression would lead to CRPC which exhibits stem-like features [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…KRT7 could act as a biomarker of a particular state, more than a marker of a distinct cellular population per se. The recent publication of a single-cell analysis of human primary prostate cancer uncovered heterogeneous cellular states in prostate epithelial cells from both cancer areas and paired-matched normal tissue adjacent to the tumor [ 59 ]. These results suggested a cellular plasticity, and either KRT17 or KRT7 were described as markers of particular cellular states (basal and club cells, respectively), thus providing some insight into a putative functional role of KRT7 [ 59 ].…”
Section: Discussionmentioning
confidence: 99%